Respuesta :

The polynomial is not factorable, so we use the quadratic formula.


x^2 + 5x − 2 = 0


[tex] x = \dfrac{-b \pm \sqrt{b^2 - 4ac}}{2a} [/tex]


[tex] x = \dfrac{-5 \pm \sqrt{5^2 - 4(1)(-2)}}{2(1)} [/tex]


[tex] x = \dfrac{-5 \pm \sqrt{25 + 8}}{2} [/tex]


[tex] x = \dfrac{-5 \pm \sqrt{33}}{2} [/tex]


[tex] x = \dfrac{-5 + \sqrt{33}}{2}~~or~~x = \dfrac{-5 - \sqrt{33}}{2} [/tex]


[tex] x = -\dfrac{5}{2} + \dfrac{\sqrt{33}}{2}~~or~~x = -\dfrac{5}{2} - \dfrac{\sqrt{33}}{2} [/tex]

ACCESS MORE